Implementasi Kids Art Space sebagai Inovasi Lingkungan Belajar dalam Pengembangan Motorik Halus Anak Usia Dini - Elva M. Sumirad; Sri Yulan Umar; Yenti Juniarti; Sri Indirawati Zakaria; Salsabila R. Solang (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
A creative and stimulating learning environment plays an important role in supporting early childhood development, particularly fine motor skills. One innovative learning environment that can be implemented is Kids Art Space, a specially designed art space that provides children with safe, enjoyable, and meaningful learning experiences through art activities. This study aims to describe the implementation of Kids Art Space as an innovative learning environment in supporting the development of fine motor skills in early childhood. The research employed a descriptive qualitative approach involving early childhood participants who took part in Kids Art Space activities, with parents serving as companions and supporting informants. Data were collected through observation, documentation, and activity reflection. The results indicate that the implementation of Kids Art Space effectively enhances children’s fine motor skills through various art activities such as sticking, painting, color mixing, and tap-tap plastic activities that involve hand–eye coordination. In addition, Kids Art Space positively influences children’s focus, enthusiasm, independence, and self-confidence during the learning process. Therefore, Kids Art Space can be considered an innovative and effective learning environment that supports fine motor development in early childhood through creative and interactive learning experiences.